Violencia intrafamiliar y su influencia en el rendimiento académico de un estudiante de educación media - Pacalla Castro, Zoila Liliana (2021)
This case study whose theme is Domestic Violence and its influence on the academic performance of a 14-year-old high school student, which aimed to establish the incidence of domestic violence in the student's poor school performance, a process of several sessions that led us to a diagnosis which was: another anxiety disorder specified with the code 300.9 (F 41 .8) in the DSMV manual. To arrive at this diagnosis, techniques were also used to collect information such as: the clinical history, the observation and the psychometric instrument: Hamilton scale for anxiety, consecutively a therapeutic scheme based on the Cognitive-Behavioral approach for the control of Anxiety was shaped in order to level their emotions and improve their academic performance.